APLIKASI JAKI SEBAGAI MEDIA PENGADUAN SARANA UMUM DI KELURAHAN JATINEGARA - Muhammad Ardya Dwi Putra Al Qindi; Noviawan Rasyid Ohorella; Edy Prihantoro; Tri Wahyu Retno Ningsih (JURNAL BADATI, 2023)
This study aims to find out how the JAKI application is used as a media for complaints about public facilities in Jatinegara Village, as well as obstacles in using the JAKI application in submitting complaints about public facilities in Jatinegara Village. The method used in this research uses qualitative methods. In writing this scientific research using the theory of diffusion of innovation and the theory of new media. Based on the results of research on government electronic applications, namely the JAKI application at the Jatinegara Sub-District level, it is a program from the DKI Jakarta Provincial Government to deal with any problems that exist in the area so that they are quickly handled, and residents stated that the use of the JAKI application was very efficient in Jatinegara Kelurahan in handling public facilities, and also responsive to every complaint reported by residents around the Jatinegara Village. The JAKI application has a variety of features, and obstacles were found such as lack of understanding of technology and the internet.